FRI0442 EFFECTIVENESS OF YTTRIUM KNEE SYNOVECTOMY IN PSORIATIC OR SERONEGATIVE ARTHRITIS WHO HAVE FAILED CONVENTIONAL THERAPY. (June 2019) - Hoey, Mark; Mcdowell, Victoria; Pendleton, Adrian
Abstract : Background: Radiation synovectomy with Yttrium 90Y is indicated for refractory arthritis of various aetiologies e.g. inflammatory joint diseases such as rheumatoid arthritis, seronegative arthritidies such as psoriatic arthritis and reactive arthritis, Haemophilic arthritis, Calcium pyrophosphate dihydrate (CPPD) arthritis and pigmented villonodular synovitis (PVNS) 1 . Treatment of inflammatory arthritis has improved due to more effective therapy and earlier treatment therefore Yttrium therapy is less commonly used. Objectives: To assess the response to Yttrium 90Y synovectomy in patients with Psoriatic arthritis or seronegative arthritis with synovitis affecting the knee joint in a cohort of patients who had failed conventional DMARDs, biological DMARDs or intra-articular steroid injections. To identify any possible predictors of good or poor response. To develop a standard operating procedure to improve consistency and also allow service to be potentially expanded. Methods: Retrospective chart and electronic care record review of all patients receiving Yttrium therapy in Northern Ireland from March 2016 to April 2018. Patient demographics, MRI findings, conventional and biological DMARD use, previous intra-articular steroid use were recorded. Patients were reviewed approximately six months following treatment. The medical notes were reviewed to decide whether there had been a good or poor response to treatment and data analyzed to look for factors that may predict response. The process was evaluated and we developed a standard operating procedure to improve consistency and safety going forward. Results: 17 patients in total received Yttrium therapy, 9 males. Age range was 18-75 with a mean 41. 10 patients were diagnosed with seronegative arthritis and 7 with psoriatic arthritis. All patients had an MRI of the affected joint(s) which confirmed synovitis in all cases. 9 MRIs showed no significant degenerative changes, 5 showed mild degenerative changes and 3 moderate/severe. All patients had previously received intra-articular steroid injection. 12 patients also were receiving or had failed treatment with a conventional or biological DMARD. Each knee received a dose of 180MBq Yttrium under direct ultrasound guidance in addition to Triamcinolone 40mg and using Lidocaine 1% local anaesthesia. 3 patients received treatment for both knees. Reviewing all patients 71% (12/17) reported good efficacy. 78% (7/9) of patients reported good efficacy in group with no osteoarthritis on MRI, 60% (3/5) in the mild osteoarthritis group and 67% (2/3) in the moderate to severe osteoarthritis group. BMI, Age, sex or underlying diagnosis did not appear to predict response in this group. There were no adverse events reported Conclusion: Yttrium therapy is not widely used with only one unit in Northern Ireland performing the procedure. The use of effective DMARDs and biological therapy has improved management of psoriatic and rheumatoid arthritis. In spite of this some patients still have refractory disease. We have shown in this observational study that in patients with knee synovitis despite treatment with DMARDs, biologics and intra-articular steroids, Yttrium synovectomy shows good efficacy, is a relatively low cost and generally safe treatment option for these patients. Going forward this study and our standard operating procedure will allow us to develop criteria to help select patients for Yttrium therapy and standardize our treatment. References: [1] Clunie G, Fischer M (2003) EANM procedure guidelines for radiosynovectomy. Eur J Nucl Med30:BP12–BP16 Disclosure of Interests: None declared